Bimetal Organic Framework–Ti3C2Tx MXene with Metalloporphyrin Electrocatalyst for Lithium–Oxygen Batteries. (26th October 2022) - Nam, Sanghee; Mahato, Manmatha; Matthews, Kyle; Lord, Robert W.; Lee, Yonghee; Thangasamy, Pitchai; Ahn, Chi Won; Gogotsi, Yury; Oh, Il‐Kwon
Abstract: The gravest oxidation of MXenes has become a critical problem due to the formation of metal oxides, leading to the loss of their intrinsic properties. Herein, bimetallic cobalt–manganese organic framework (CMT) directly grown on a Ti3 C2 Tx MXene sheet via solvothermal treatment to obtain strong oxidation resistance in an open structured application and to enhance electrocatalytic properties for oxygen evolution and reduction reaction is reported. Inspired by ligand chemistry, the carboxyl acids in tetrakis(4–carboxyphenyl)porphyrin acting as an organic linker are grafted with the surface terminators of Ti3 C2 Tx MXene through the Fischer esterification and substitution reaction of fluorine, thereby greatly enhancing the antioxidation stability. Furthermore, the as‐formed metalloporphyrin structure and unpaired electrons, produced between CMT and Ti3 C2 Tx MXene during solvothermal treatment, improve their electrocatalytic activity, durability, and electrical conductivity through an electron hopping mechanism. Consequently, the CMT@MXene demonstrates high stability as a bifunctional electrocatalyst at a fixed specific capacity of 1000 mAh g −1 and a current density of 500 mA g −1 for 247 cycles in lithium–oxygen (LiO2 ) battery. This approach suggests new strategies for the synergistic coupling of MXenes and MOFs for future open structured applications. Abstract : Mutually cross‐linked MXene and bimetal organic framework by Fischer esterification and substitution reaction of fluorine is utilized to improve the oxidation stability and applied as a bifunctional electrocatalyst in LiO2 batteries. It demonstrates improved antioxidation, overpotentials (1.007 and 0.243 V for oxygen evolution reaction and oxygen reduction reaction, respectively), and remarkable cycling stability (312 cycles) due to improved adsorption and desorption by unpaired electrons and the highly durable metalloporphyrin structure.